2016
DOI: 10.1111/pan.13041
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of propofol alone to propofol in combination with dexmedetomidine for pediatric 3T MRI sedation

Abstract: The addition of a dexmedetomidine infusion prior to our propofol MRI sedation protocol resulted in fewer sedation-related adverse events, particularly upper airway obstruction. Further studies are needed to evaluate the potential for a reduction on adverse events with this drug combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 32 publications
(58 reference statements)
1
50
0
1
Order By: Relevance
“…This result is comparable to other studies using dexmedetomidine (1 lg/kg) bolus. 18,22 In a recent study reported by Borosi, the addition of dexmedetomidine (1 lg/kg) significantly prolonged discharge time. In our study, the low-dose dexmedetomidine bolus did not affect recovery time, even with second bolus ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This result is comparable to other studies using dexmedetomidine (1 lg/kg) bolus. 18,22 In a recent study reported by Borosi, the addition of dexmedetomidine (1 lg/kg) significantly prolonged discharge time. In our study, the low-dose dexmedetomidine bolus did not affect recovery time, even with second bolus ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Dexmedetomidine has been reported to reduce propofol plasma concentrations and dose required for sedation and suppression of motor response in healthy subjects. In a pediatric study, dexmedetomidine combined with propofol infusion reduced total propofol dose and decreased the incidence of airway complications . We also wanted to explore the effect of low‐dose dexmedetomidine on hemodynamic parameters from preinduction to up to 60 minutes after induction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several studies that have examined sedation concepts in children undergoing diagnostic imaging or procedures requiring deep sedation, the current study is to our knowledge is the first randomized clinical trial with a double‐blinded design to compare the 2 propofol sedation regimens with and without ketamine added at induction. Aside from preexisting personal or institutional preference, there are different rationales for each sedation concept.…”
Section: Discussionmentioning
confidence: 99%
“…There were no anesthesia-related serious complications (aspiration, cardiac arrest, and death) were seen in preschool and school children in recommended doses. Previously, various techniques were tried for procedural anesthesia like general anesthesia with tracheal intubation or laryngeal mask, -controlled analgesia with fentanyl and infusion of propofol or dexmedetomidine but there was no significant eminence of one of them over the others [8,9,10]. A comprehensive safety, rapid onset of action, a short duration action, and quick recovery time with no adverse effects are the main characteristics of the ideal anesthetic agent for procedural sedation.…”
Section: Discussionmentioning
confidence: 99%